Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1182/blood.v92.9.3137
|View full text |Cite
|
Sign up to set email alerts
|

Anti–B-Cell Monoclonal Antibody Treatment of Severe Posttransplant B-Lymphoproliferative Disorder: Prognostic Factors and Long-Term Outcome

Abstract: B-lymphoproliferative disorder (BLPD) is a rare but severe complication of organ and bone marrow transplantation (BMT). Profound cytotoxic T-cell deficiency is thought to allow the outgrowth of Epstein-Barr virus–transformed B cells. When possible, reduction of immunosuppressive treatment or surgery for localized disease may cure BLPD. Therapeutic approaches using chemotherapy or antiviral drugs have limited effects on survival. Adoptive immunotherapy with donor T-cell infusions has given promising results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(45 citation statements)
references
References 48 publications
5
39
0
1
Order By: Relevance
“…Early reports suggested that these potentially malignant lymphoid proliferations responded to reduced immune suppression in children and normal intensive B cell lymphoma therapy in adults [10,11]. Immunotherapy with early B cell antibodies was also explored with some success [12]. Over the last 10 years it has become clear that PTLD is amenable to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports suggested that these potentially malignant lymphoid proliferations responded to reduced immune suppression in children and normal intensive B cell lymphoma therapy in adults [10,11]. Immunotherapy with early B cell antibodies was also explored with some success [12]. Over the last 10 years it has become clear that PTLD is amenable to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…41 The potential for exacerbation of rejection with interferon, toxicity with chemotherapy, and logistic problems with cell-based therapy make antibody therapy attractive. With the unavailability of anti-CD21 and anti-CD24 monoclonal antibodies, 48 anti-CD20 monoclonal antibody therapy has been used instead and recently was reported to be of some benefit in post-LT PTLD. 49 Chemotherapy may be necessary for refractory PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…[100][101][102] Factors shown to predict a favourable response to rituximab include a short duration between organ transplantation and onset of PTLD, localised disease, absence of CNS involvement, and a normal serum LDH level. 102,103 Rituximab has been used simultaneously with other treatments including chemotherapy or sirolimus (as monotherapy to prevent allograft rejection) which appear promising with improved response rates. 104,105 Preemptive treatment with rituximab has been evaluated in HSCT recipients (but not in SOT recipients) with high EBV viral load, demonstrating a decrease in incidence of PTLD from 49% to 18% compared to a historical cohort.…”
Section: Rituximabmentioning
confidence: 99%